2015
DOI: 10.12998/wjcc.v3.i9.823
|View full text |Cite
|
Sign up to set email alerts
|

Sports hernia and femoroacetabular impingement in athletes: A systematic review

Abstract: The restriction in range of motion due to FAI likely contributes to sports hernias; therefore, surgical treatment of both pathologies represents an optimal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 82 publications
1
17
0
4
Order By: Relevance
“…One study reported FAI and concomitant sports hernias occurring in 12% to 94% of patients, with the combined laparoscopic/arthroscopic management of both conditions demonstrating superior return-to-play rates (89% vs 33%, respectively) over the individual management of either abnormality. 62…”
Section: Resultsmentioning
confidence: 99%
“…One study reported FAI and concomitant sports hernias occurring in 12% to 94% of patients, with the combined laparoscopic/arthroscopic management of both conditions demonstrating superior return-to-play rates (89% vs 33%, respectively) over the individual management of either abnormality. 62…”
Section: Resultsmentioning
confidence: 99%
“…FAI syndrome and inguinal pathologies were previously considered to be two separate clinical entities, but recent studies have suggested that both of these clinical conditions can exist simultaneously in athletes affected by GPS [ 7 , 12 , 20 , 60 ]. It was recently shown that a cam deformity may be associated with GPS, especially in young high-level athletes [ 19 , 32 , 57 , 59 62 ]. The strong association between the cam deformity and inguinal pathologies (88.6%) found in this study confirms findings from previous studies [ 21 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…2,7 Further complicating the presentation is the possibility of multiple coexisting diagnoses 3 and regional interdependence as a contributing factor to local pain and impairment, 8 as well as global movement system dysfunction. It has been found that up to 94.1% of athletes diagnosed with athletic pubalgia have radiographic evidence of femoral acetabular impingement (FAI) 9,10,11 while hip and groin pathology and low back pain have been proposed to be found concurrently in the same patient population. 12,13,14,15 Multiple diagnostic methods and modalities, 7,15,16,17 including a layered pathoanatomical approach, 1 have been proposed to help clarify the identification of specific diagnoses, guide treatment, and explain potential mechanisms of injury within the hip and lumbopelvic region.…”
Section: Introductionmentioning
confidence: 99%
“…15,18 This anatomical presentation may result in abnormal hip ROM, which has been suggested as a risk factor for many of the previously noted injuries, such as intra-articular hip, core and adductor related injury, and LBP. 1,2,11,19 However, these bony and intraarticular features have also been identified in a large proportion of asymptomatic athletes and may not be solely responsible for pathology. 20 Athletes with asymptomatic hips have commonly been reported to present with cam (54.6%) and pincer (49.5%) morphology respectively, while 65.4% were found to have an acetabular labrum defect.…”
Section: Introductionmentioning
confidence: 99%